CHARACTER VALUE DISCOURSE IN BALI'S POP SONG AND DENPASAR CITY’S PUBLIC RECEPTION - Sri Marheni, Komang; Wirawan, A.A. Bagus; Anom Kumbara, A.A. Ngurah; Suarka, I Nyoman (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2019)
Character discourse surfaced in response to globalization. Balinese pop songs also contribute to discourse of character values ??in the context of the mass culture industry. This study reveals the ideology, form, and reception of people in Denpasar on the discourse of character values ??in Balinese pop songs. Through a qualitative method with a critical discourse analysis approach based on the semiotic theory, deconstruction, and reception aesthetics, it was concluded that the ideology that constructs the discourse of character values ??in Balinese pop songs includes religious ideology, Ajeg Bali, capitalists, and mass media within the scope of industrialization of mass culture. Forms of character value discourse in Balinese pop songs include the value of religious, nationalist, independent, mutual cooperation, and integrity in various song themes. The public reception in Denpasar on the discourse of character values ??is relatively diverse and ambiguous, both to the meaning of song, capitalist power, producer power, and to the power of the mass media. This study found that the discourse of character values ??in Balinese pop songs reflects ideological construction in the mass culture industry. There is a tendency to shift from the meaning of the song to the aesthetic and artistic realm in accordance with consumer responses. The theory of moral criticism of mass culture is confirmed that the discourse of character values ??in Balinese pop songs can be developed by negotiating meaning, aesthetics, and artistic. Keywords: discourse, character values, Balinese pop song, reception of community